‘G’ followed by ‘H’-gout follows homoeopathy - Tripathy, Tridibesh; Das, Shankar; Singh, D. P.; Prusty, Umakant; Pattnaik, Jeevan Krushna; Bihary Pradhan, Pramod; Dubey, Anil; Kumar, Anjani; Tripathy, Sanskriti; Tripathy, Anjali; Dwivedi, Rakesh; Gautam, Mohini (International Journal of Research in Medical Sciences, 2023)
Currently in modern medicine, it is seen that taking a uric acid reducing drug during an attack of gout actually prolongs the pain and discomfort. So, the learning is that one need not worry about high uric acid levels during an acute flair of gout. What actually someone needs is an anti-inflammatory that reduces the inflammation caused by the crystals of uric acid that build up in the joints when someone has gout. This anti-inflammatory drug is ‘colchicine’. Homoeopathy has been using the drug ‘colchicum autumnale’ for last 233 years since its discovery in 1790 by Dr. Samuel Hahnemann (1755-1843). It also uses its active principle ‘colchicine’ for the last 233 years. It is quite striking to see that the modern medicine is realizing the importance of ‘colchicine’ currently. The same ‘colchicine’ was advised to be used as an anti-inflammatory to reduce the markers like C-reactive protein, LDH, D-dimer and homocysteine. During the COVID-19 peak, again the homoeopathic Colchicine came to the rescue. The current article examines the use of homoeopathy in gout and uric acid problems and again at a larger issue with the protein metabolism and the kidney heath. Integration of homoeopathy at large scale will help the nation to protect its members from protein metabolism disorders, kidney health and gout as well.